Communication of the Judiciary - Fekete, Kristóf Benedek (Essays of Faculty of Law University of Pécs, Yearbook of [year], 2023)
The author describes the limitations of the freedom of expression of judges and courts in the context of the fundamental right to freedom of expression, which, due to its prominent position in a democratic constitutional state, is limited in content compared to the general one, also in view of the historical precedents in Hungary. Starting from the relevant constitutional and statutory provisions and in the light of the practice of the Venice Commission and the European Court of Human Rights, the study outlines and analyses the possibilities for individual judges and courts to express their opinions. The paper presents, through a number of pragmatic examples, the prevailing practice in Hungary on the subject under study, which works with undoubtedly one of the most stringent regulatory solutions.